2022
DOI: 10.1186/s12888-022-03809-2
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 severity and age increase the odds of delirium in hospitalized adults with confirmed SARS-CoV-2 infection: a cohort study

Abstract: Background Despite recognition of the neurologic and psychiatric complications associated with SARS-CoV-2 infection, the relationship between coronavirus disease 19 (COVID-19) severity on hospital admission and delirium in hospitalized patients is poorly understood. This study sought to measure the association between COVID-19 severity and presence of delirium in both intensive care unit (ICU) and acute care patients by leveraging an existing hospital-wide systematic delirium screening protocol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
(28 reference statements)
2
7
0
2
Order By: Relevance
“…Previous studies have shown neurological manifestations such as delirium were found to be associated with more severe disease presentation and higher mortality rates. 23,24 This suggests delirium is an indicator of a poorer prognosis in COVID-19 patients, which is consistent with previous studies though these studies tend to be oriented towards older patient populations. 3,16,17 This study showed delirium was significantly associated with worse patient outcomes including longer hospital stay, longer ICU stay, higher rates of mechanical ventilation, more days on mechanical ventilation and higher mortality in this younger, predominantly Hispanic population.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Previous studies have shown neurological manifestations such as delirium were found to be associated with more severe disease presentation and higher mortality rates. 23,24 This suggests delirium is an indicator of a poorer prognosis in COVID-19 patients, which is consistent with previous studies though these studies tend to be oriented towards older patient populations. 3,16,17 This study showed delirium was significantly associated with worse patient outcomes including longer hospital stay, longer ICU stay, higher rates of mechanical ventilation, more days on mechanical ventilation and higher mortality in this younger, predominantly Hispanic population.…”
Section: Discussionsupporting
confidence: 89%
“…Our results are consistent with previous literature that indicates delirium is associated with worse health outcomes in COVID-19 patients. 16,22,24 In terms of psychiatric history, patients diagnosed with delirium had pre-existing cognitive deficits and history of substance use. Cognitive deficits have been found in older patients to be associated with development of delirium, and we see here a confirmation of studies suggesting that association is also true in younger patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estudos confirmam que a síndrome aguda grave por coronavírus pode ser responsável por doenças neurológicas, devido a um efeito direto da invasão viral no sistema nervoso central, a mediadores inflamatórios induzidos pela infecção, a fatores da doença e do próprio tratamento para Covid-19. Devido a isso os pacientes podem apresentar alterações da consciência e distúrbios de cognição (Benussi et al, 2020;Helms et al, 2020;Hariyanto et al, 2021;Shao et al, 2021;Lahue et al, 2022).…”
Section: Discussionunclassified
“…Ainda, Neto et al (2021) Finalmente, vale ressaltar que a investigação do tratamento ou prevenção do delirium é crucial e implementa práticas para recuperação. Assim, é de importância dos profissionais de saúde a avaliação do delirium e a monitoração dos sintomas em pacientes com Covid-19, a fim de que ocorra uma organização e um diagnóstico precoce desses pacientes, evitando o alto índice de mortalidade (Benussi et al, 2020;Helms et al, 2020;Hariyanto et al, 2021;Shao et al, 2021;Lahue et al, 2022).…”
Section: Discussionunclassified